Relationships between maximal anaerobic power of the arms and legs and javelin performance - Bouhlel, E.; Chelly, M. S.; Tabka, Z.; Shephard, R. (The Journal of Sports Medicine and Physical Fitness, 2007)
Aim: The aim of this study was to examine relationships between maximal anaerobic power, as measured by leg and arm force-velocity tests, estimates of local muscle volume and javelin performance. Methods: Ten trained national level male javelin throwers (mean age 19.6± 2 years) participated in this study. Maximal anaerobic power, maximal force and maximal velocity were measured during leg (Wmax-L) and arm (Wmax-A) force-velocity tests, performed on appropriately modified forms of Monark cycle ergometer. Estimates of leg and arm muscle volume were made using a standard anthropometric kit. Results: Maximal force of the leg (Fmax-L) was significantly correlated with estimated leg muscle volume (r=0.71, P<0.05). Wmax-L and Wmax-A were both significantly correlated with javelin performance (r=0.76, P<0.01; r=0.71, P <0.05, respectively). Maximal velocity of the leg (Vmax-L) was also significantly correlated with throwing performance (r=0.83; P<0.001). Conclusion: Wmax of both legs and arms were significantly correlated with javelin performance, the closest correlation being for Wmax-L; this emphasizes the importance of the leg muscles in this sport. Fmax-L and Vmax-L were related to muscle volume and to javelin performance, respectively. Force-velocity testing may have value in regulating conditioning and rehabilitation in sports involving throwing.